2018
DOI: 10.5230/jgc.2018.18.e17
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Totally Laparoscopic Radical Gastrectomy for Advanced Gastric Cancer: Comparison with Early Gastric Cancer

Abstract: PurposeTotally laparoscopic gastrectomy (TLG) for advanced gastric cancer (AGC) is a technically and oncologically challenging procedure for surgeons. This study aimed to compare the oncologic feasibility and technical safety of TLG for AGC versus early gastric cancer (EGC).Materials and MethodsBetween 2011 and 2016, 535 patients (EGC, 375; AGC, 160) underwent curative TLG for gastric cancer. Clinicopathologic characteristics and surgical outcomes of both patient groups were analyzed and compared.ResultsPatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…With the development of laparoscopic instruments, totally LTG (TLTG) using linear staplers has recently become popular. Our center reported that the short-term outcome of TLTG was not inferior to that of LATG and that TLTG could be safely performed in patients with AGC [28,29]. Nakauchi et al [10] also reported their experience with TLTG in 92 patients; the results supported the technical feasibility of TLTG and acceptable 3-year follow-up results.…”
Section: Discussion/conclusionsupporting
confidence: 52%
“…With the development of laparoscopic instruments, totally LTG (TLTG) using linear staplers has recently become popular. Our center reported that the short-term outcome of TLTG was not inferior to that of LATG and that TLTG could be safely performed in patients with AGC [28,29]. Nakauchi et al [10] also reported their experience with TLTG in 92 patients; the results supported the technical feasibility of TLTG and acceptable 3-year follow-up results.…”
Section: Discussion/conclusionsupporting
confidence: 52%
“…Recently, many retrospective comparative studies and several prospective RCTs have reported that LG for AGC was safe and feasible when compared to the short-term and long-term outcomes observed with OG [2][3][4][5][6][7][8][9][10][11][12][13] . Table 1 summarizes these studies about LG for AGC in recent years.…”
Section: Previous Studies About Radical Lg For Agcmentioning
confidence: 99%
“…Especially, some authors demonstrated the technical safety of LDG with D2 LND for locally AGC in the multi-institutional, prospective, phase II study [2][3][4][5]11] . Moreover, the 3-year or 5-year overall or disease-free survival rates have been gradually reported from China, Korea, and Japan [7][8][9][10][11][12][13] . Majority of them reported that LG is feasible and safe for the treatment of AGC with D2 LND compared with OG, and no significant differences were observed in long-term over all survival (OS) and disease free survival (DFS) between the LG group and OG group.…”
Section: Previous Studies About Radical Lg For Agcmentioning
confidence: 99%
“…Patients experience less estimated blood loss, milder postoperative pain, and shorter hospital stays with TLG compared with laparoscopy-assisted gastrectomy. 4 Delta-shaped gastroduodenostomy (DA) is recognized as one of the most common reconstruction methods in Japan and Korea. 5 However, the application of DA in China remains restricted as patients are often diagnosed at late tumor stages.…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of more advanced instruments, totally laparoscopic gastrectomy (TLG) is increasingly popular. Patients experience less estimated blood loss, milder postoperative pain, and shorter hospital stays with TLG compared with laparoscopy‐assisted gastrectomy 4 . Delta‐shaped gastroduodenostomy (DA) is recognized as one of the most common reconstruction methods in Japan and Korea 5 .…”
Section: Introductionmentioning
confidence: 99%